Leveraging Network Capital for Global Expansion: Evidence from Chinese High-tech SMEs - Ju, Hang; Abd Rani, Shamsul Huda; Abu Hassan, Mohamad Hanif (International Review of Management and Marketing, 2026)
This empirical investigation examines the multidimensional influence of network capital on the internationalization performance of Chinese high-technology small and medium enterprises (SMEs), with government policy functioning as a critical moderating mechanism. Drawing upon the resource-based view, social capital theory, and institutional theory, we develop and test a comprehensive theoretical framework that disaggregates network capital into three distinct yet interrelated dimensions: availability of network resources, access to market opportunities, and access to collaborative partnerships. Employing a cross-sectional survey design, we collected primary data from 342 high-technology SMEs operating in Shenzhen, China’s premier innovation ecosystem. Through structural equation modeling and multi-group moderation analysis, our empirical findings reveal that all three dimensions of network capital exert statistically significant positive effects on SME internationalization performance. Furthermore, government policy support demonstrates differential moderating effects, significantly amplifying the relationships between network resource availability and internationalization and between market opportunity access and internationalization, while exhibiting no significant moderation effect on the collaboration-internationalization nexus. These findings contribute to the international business literature by elucidating the boundary conditions under which network capital facilitates SME internationalization in emerging economies. The study offers actionable insights for policymakers designing targeted internationalization support programs and for SME managers strategically leveraging network resources for global expansion.